2013
DOI: 10.1140/epje/i2013-13075-2
|View full text |Cite
|
Sign up to set email alerts
|

Bending stiffness of biological membranes: What can be measured by neutron spin echo?

Abstract: Large vesicles obtained by the extrusion method represent adequate membrane models to probe membrane dynamics with neutron radiation. Particularly, the shape fluctuations around the spherical average topology can be recorded by neutron spin echo (NSE). In this paper we report on the applicable theories describing the scattering contributions from bending-dominated shape fluctuations in diluted vesicle dispersions, with a focus on the relative relevance of the master translational mode with respect to the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 69 publications
8
35
0
Order By: Relevance
“…ZG showed that, when governed by bending elasticity, the intermediate scattering function of the membrane fluctuations decays as a stretched exponential at short length and time scales. Such a decay has been observed in experiments on microemulsion systems [37,38,39], lamellar bilayer phases [40,41] and vesicles [22,23,31,42,43]. However, a similar theory for hybrid curvaturedilational modes is still lacking.…”
Section: Vesicle Fluctuation Dynamicsmentioning
confidence: 78%
See 2 more Smart Citations
“…ZG showed that, when governed by bending elasticity, the intermediate scattering function of the membrane fluctuations decays as a stretched exponential at short length and time scales. Such a decay has been observed in experiments on microemulsion systems [37,38,39], lamellar bilayer phases [40,41] and vesicles [22,23,31,42,43]. However, a similar theory for hybrid curvaturedilational modes is still lacking.…”
Section: Vesicle Fluctuation Dynamicsmentioning
confidence: 78%
“…The fluctuation dynamics of lipid vesicles spans many different spatiotemporal domains, ranging from the macroscopic scale, where the shape fluctuations can be directly observed under the optical microscope, down to the molecular scale. In the microscopic scale, a combination of inelastic neutron scattering [31] and molecular dynamics (MD) simulation [32,33] offers a congruent description of the molecular structure and the fundamental transport process involved in the mechanical response of the lipid bilayer. In the macroscopic regime, flickering spectroscopy (FS) provides an inestimable tool to probe membrane dynamics both in giant unilamellar vesicles (GUVs) and in real cells [34].…”
Section: Vesicle Fluctuation Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding analysis is model-based and produces bending rigidities similar to those obtained from GUV pipette aspiration [23]. An alternative dynamic technique, NSE, is characterized by correlation times and length scales that are very similar to those of membrane thermal fluctuations, and measures bending rigidity from neutron scattering as a function of Fourier time [24]. A detailed description of these experimental methods can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane raft model structures with tuneable compositions were characterised by neutron diffraction and reflectivity [5], while raft dynamics in large uni-lamellar vesicles in interaction with beta amyloid peptide was observed by the neutron spin echo method combined with small angle scattering [6]. The bending stiffness of biological membranes as determined by neutron spin echo is also presented [7]. Two contributions [8,9] report on undulation dynamics and shape fluctuations, respectively, in lipid vesicles as a function of lipid composition and other parameters observed by neutron spin echo in combination with other methods like small angle scattering and light scattering.…”
mentioning
confidence: 99%